Comparison of mini-bestest and dynamic gait index for prediction of fall susceptibility in old individuals - Miqdad, .; Pawar, Sushil Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Emphasis on early identification, prevention, and intervention of fall risk in elderly people is becoming increasingly important in the fields of physical therapy and rehabilitation. Methods: Various scales are currently used for assessment of balance and fall risk. We have selected, MiniBESTest and DGI for our present study. We compared scores of Mini-BESTest and DGI in 30 elderly subjects with mean age of 62.23±4.38yrs. These subjects included 17 completely normal individuals, whereas 13 subjects were having early clinical features of fall-related disorders. Example: Parkinsonism, vertigo and paresis. Results: The data indicated that Mini-BESTest is more superior than DGI to indicate the fall risk in normal elderly population. Similarly, in cases of paresis and Parkinsonism, results are indicating that Mini-BESTest is better suited than the DGI. But in cases of vertigo, the results indicate that DGI is more superior than Mini-BESTest. Conclusions: An interesting finding is that the DGI scale seems to be more superior in subjects having vertigo (Refer Table-4), which is to be verified by further studies in a larger sample. The point which justifies the above conclusion is that the DGI scale includes many items which test the vestibular apparatus.